First detection of the Africa/Caribbean/Latin American subtype of Culex flavivirus in Asian country, Taiwan - Chen, Yi-Ying; Lin, Jen-Wei; Fan, Yi-Chin; Tu, Wu-Chun; Chang, Gwong-Jen J.; Chiou, Shyan-Song (Comparative immunology, microbiology and infectious diseases, 2013)
Culex flavivirus (CxFV), a member of the genus flavivirus, is a novel insect-specific flaviviruses that can be divided into two subtypes, the cytopathic Asia/U.S. and the noncytopathic Africa/Caribbean/Latin American subtypes. The CxFV circulates in several Asian countries, and here we conducted the first study investigating CxFV in Taiwan. A total of 14,016 mosquitoes were collected between 2010 and 2012 and 3.4% (6/179) of the pools were CxFV-positive. The phylogenetic analyses indicate that the Taiwan isolates are closely related to the Africa/Caribbean/Latin American subtype, but form an independent cluster. In the cytology experiments, the CxFV Taiwan isolate infected only mosquito cells and caused cell–cell fusion that might be associated with a unique glycine residue at position 117 within the envelope protein, which is shared with the cytopathic effect-causing Asia/US subtype. This study marks the first time the Africa/Caribbean/Latin American subtype of CxFV has been identified in an Asian country and grouped into a novel cluster.